2017
DOI: 10.3390/cryst7060175
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a New Cobaloxime-Terpyridine Compound

Abstract: Abstract:A new cobaloxime was synthesized by the reaction of cobalt chloride and diphenylglyoxime in methanol, followed by the addition of 4 -(4-pyridyl)-2,2 :6 ,2 -terpyridine, pytpy. This complex was characterized by UV-Vis spectroscopy, 1 H-NMR spectroscopy, cyclic voltammetry, and single-crystal X-ray diffraction analysis. In cyclic voltammetry experiments an irreversible reduction wave assigned to Co(III)/Co(II) at Ecp = −0.31 V vs. Ag/AgCl and a quasi-reversible process assigned to the Co(II)/Co(I) reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Wiedner et al in 2016, [42] studied the electrochemistry and electrocatalytic activity of the complex Co(II)(dmgBF 2 ) 2 (CH 3 CN) 2 (33). The cyclic voltammogram of the complex (33) showed a reversible peak for Co(II)/Co(I) couple and the CV was recorded in different scan rates, which confirmed the experiment was purely diffusion controlled.…”
Section: Electrochemistry and Electrocatalytic Activity Of Cobaloximesmentioning
confidence: 84%
See 4 more Smart Citations
“…Wiedner et al in 2016, [42] studied the electrochemistry and electrocatalytic activity of the complex Co(II)(dmgBF 2 ) 2 (CH 3 CN) 2 (33). The cyclic voltammogram of the complex (33) showed a reversible peak for Co(II)/Co(I) couple and the CV was recorded in different scan rates, which confirmed the experiment was purely diffusion controlled.…”
Section: Electrochemistry and Electrocatalytic Activity Of Cobaloximesmentioning
confidence: 84%
“…The linear plot of the scan rate against peak current revealed that the process was diffusion controlled. [40] Rountree et al, in 2016 [41] performed kinetic analysis of hydrogen production catalyzed by Co(dmgBF 2 ) 2 (CH 3 CN) 2 (33). The CV of the complex showed a reversible one electron reduction process of Co(II)/Co(I) and an irreversible peak attributed to Co(III)/Co(II).…”
Section: Electrochemistry and Electrocatalytic Activity Of Cobaloximesmentioning
confidence: 99%
See 3 more Smart Citations